Notes on new record of orchids on the summit of Gunung Jerai, Kedah, Peninsular Malaysia - Auyob, Nur Adilah; Zulkifli, Syaizwan Zahmir; Nordin, Farah Alia; Annathurai, Vhenosha; Ong Abdullah, Janna; Yong, Christina Seok Yien; Go, Rusea (Malaysian Nature Society, 2016)
Gunung Jerai, Kedah is one of the isolated peaks in Peninsular Malaysia. Although many botanists and collectors have explored Gunung Jerai for more than 150 years, no study was specifically conducted on the diversity of orchids in the area. The purpose of this study is to produce an updated checklist of the orchids focusing only the summit area from 700m above sea level upwards.The samples were collected along the trails and covered 5m on both sides of the trail. A total of 74 species of orchids from 40 genera were collected and identified, of which 11 species are new records to Kedah and two species are new records to Malaysia namely, Bulbophyllum sigaldiae and Liparis geophila. The total area covered was only 0.34% of Gunung Jerai’s summit region with H’ value of 3.424. The presence of all five subfamilies of Orchidaceae collected within a small area indicates that the species at the summit region are fairly diverse and abundant. The result of this study implied the poor record of orchid flora in Gunung Jerai, even though it has been botanized for more than a century. The discovery of the new records however, indicates that the summit region of Gunung Jerai is a prolific region for orchid species to flourish. Hence, it is no doubt Gunung Jerai as a whole harbours a very rich orchid species and more comprehensively study is needed in order to unveil the true status of diversity that could be utilized as data to support a sound conservation endeavors.